Complications and Long-Term Outcomes after Combined Tibial Plateau Leveling Osteotomy and Tibial Tuberosity Transposition for Treatment of Concurrent Cranial Cruciate Ligament Rupture and Grade III or IV Medial Patellar Luxation - Redolfi, Giovanna; Grand, Jean-Guillaume (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objectives This study aims to report complications and long-term outcomes of combined tibial plateau leveling osteotomy and tibial tuberosity transposition (TPLO-TTT) for treatment of concurrent cranial cruciate ligament rupture and medial patellar luxation (MPL).Study Design This is a retrospective study. Dogs that underwent TPLO-TTT for treatment of combined cranial cruciate ligament rupture and grade III or IV MPL were included. Signalment, fixation method, and complications were recorded. Long-term outcome assessment (minimum 1 year postoperatively) was performed through clinical and radiographic reexamination at the authors' institution.Results Twenty-four stifles (22 dogs) were included. Twenty-one stifles had a grade III MPL, and 3 stifles had grade IV MPL. Four major complications consisting of surgical site infection (n = 3) and recurrent grade II MPL (n = 1) were observed. Dogs with surgical site infections were successfully treated with implant removal and oral antibiotics. No additional surgery was performed for the patient with recurrent MPL as no signs of lameness were observed. Minor complications occurred in five cases. At long-term evaluation (median: 27 months; range: 12–67 months), 21/22 dogs were clinically sound and 23/24 stifles had a complete resolution of MPL.Conclusion TPLO-TTT can be considered as an effective surgical option to treat patients with concurrent cranial cruciate ligament rupture and MPL with a relatively low major complication rate. Owners should be warned of the potential need for implant removal.
Keywords: tibial plateau levelling osteotomy; tibial tuberosity transposition; cranial cruciate ligament rupture; medial patellar luxation; dog